Overview Pterygium - Ilmawati, Ilmawati (Jurnal Health Sains, 2024)
Pterygium is a wing-shaped fibrovascular growth extending from the conjunctiva onto the cornea. This review aims to provide a comprehensive overview of pterygium, including its etiology, clinical presentation, diagnosis, treatment options, and prognosis. A literature search was conducted using PubMed and Google Scholar databases. Findings suggest that pterygium is primarily associated with UV exposure and occurs more frequently in tropical and subtropical regions. Diagnosis is primarily clinical, with treatment options ranging from conservative management to surgical intervention. While generally benign, pterygium can cause visual disturbances and has a significant recurrence rate post-surgery.